Každému zvířeti milující domov.: Občanská angažovanost zakladatelek útulků pro psy a kočky - Urbanová, Adéla (Lidé města, 2024)
This paper presents the findings of a qualitative study focused on the civic engagement of founders of associations operating dog and cat shelters. The author approaches the topic from the perspective of civil society studies, viewing it through the lens of social movements, utilizing models that analyze the relationship between volunteering and activism, and drawing on the political theory of animal rights, as developed in the concept of Zoopolis by Sue Donaldson and Will Kymlicka (2011). These approaches allow the author to capture the activist dimension of the shelter founders’ activities and to demonstrate how they challenge the legitimacy of power asymmetry in humananimal relationships. Although the principle of the “consent of the governed” has penetrated the relationship between humans and nature, civil society has never included animals or other non-human actors. However, the founders of private shelters treat the animals in their care as unique individuals, as beings with personality and agency who can and are invited to participate in decisions that affect their lives. Viewed in this way, the civic engagement of shelter founders raises questions about the boundaries of civil society, specifically the possibility of opening civil society to non-human species, even if they are only taking the first steps.